PENGARUH MEMBUTSIR TANAH LIAT TERHADAP KEMAMPUAN MOTORIK HALUS DI TAMAN KANAK-KANAK PERTIWI I KANTOR GUBERNUR KOTA PADANG - Intan Fadillah; Farida Mayar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the extent to which clay modeling activities influence the development of fine motor skills in early childhood. This study uses an observational method by conducting direct surveys of early childhood children, and the data obtained is then compared with the ideal conditions. It was found that 34 children, namely 17 children in the experimental class and 17 children in the control class, had not yet achieved optimal fine motor development. In the experimental class, 76.45% of children and in the control class, 82.35% of children were in the sufficient and needing guidance categories. The low fine motor skills of children in both classes, which were above 75%, were not yet optimally developed, and the lack of stimulation provided caused the aspect of fine motor development in children to not develop optimally, so research was needed to develop the aspect of fine motor development in children at Pertiwi Kindergarten I, Padang City Governor's Office. The researcher conducted a 5W1H analysis to obtain a clear picture of what was happening to the children. The activity of molding clay can develop children's fine motor skills. The activity of molding clay is a strategic solution to stimulate the development of children's fine motor skills